Patent Information Service Strategies of Academic Libraries Oriented to Patent Supply Chain - ZENG Jinjing, LIU Tian, ZHANG Rui (Nongye tushu qingbao xuebao, 2021)
[Purpose/Significance] The overall planning and targeted patent information services provided by university libraries play an important role in promoting the management efficiency of national scientific and technological innovation. [Method/Process] By summarizing the mode and process of patent output in universities, this study constructed the model of academic patent supply chain, discussing the information service strategies oriented to university patent supply chain. [Results/Conclusions] The results show that technological trend analysis plays a significant role in improving patent conversion rate. When patent maintenance time is long, patent licensing rate or the average profit value of patent conversion is reduced, scientific evaluation has an effect on improving the quality of patent conversion. When the user's patent awareness or technology acceptance ratio coefficient is contrary to the changing trend of the number of patent applications or conversion, policy feedback measures should be taken to maintain patent quality. Based on the above conclusions, this study puts forward some countermeasures and suggestions from the aspects of expanding the service system, strengthening the data ability and increase exports.